Different Alterations of Cerebral Regional Homogeneity in Early-Onset and Late-Onset Parkinson's Disease - Sheng, Ke; Fang, Weidong; Zhu, Yingcheng; Shuai, Guangying; Zou, Dezhi; Su, Meilan; Han, Yu; Cheng, Oumei (Frontiers in Aging Neuroscience, 2016)
Abstract Objective: Early-onset Parkinson’s disease (EOPD) is distinct from late-onset PD (LOPD) as it relates to the clinical profile and response to medication. The objective is to investigate whether characteristics of spontaneous brain activity in the resting state are associated with the age of disease onset. Methods: We assessed the correlation between neural activity and age-at-onset in a sample of 39 PD patients (18 EOPD and 21 LOPD) and 37 age-matched normal control subjects. Regional homogeneity (ReHo) approaches were employed using ANOVA with two factors: PD and age. Results: In the comparisons between LOPD and EOPD, EOPD revealed lower ReHo values in the right putamen gyrus and higher ReHo values in the left superior frontal gyrus. Compared with age-matched control subjects, EOPD exhibited lower ReHo values in the right putamen and higher ReHo values in the left inferior temporal gyrus; however, LOPD showed lower ReHo values in the right putamen and left insula. The ReHo values were negatively correlated with the UPDRS total scores in the right putamen in LOPD, but a correlation between the ReHo value and UPDRS score was not detected in EOPD. Conclusions: Our findings support the notion that age at onset is associated with the distribution of cerebral regional homogeneity in the resting state and suggest that disproportionate putamen alterations are more prominent in patients with a younger age of onset.